North-eastern Aegean sea: an effort to estimate steady-state N & P budgets during September 1998 - KRASAKOPOULOU, E.; ZERVAKIS, V.; SOUVERMEZOGLOU, E.; GEORGOPOULOS, D. (Mediterranean Marine Science, 2002)
The north-eastern Aegean sea, characterised by a complex topographical structure, is the area where highly saline waters of Levantine and South-Central Aegean origin are diluted by the outflowing through the Dardanelles of less saline waters of Black Sea origin and by river runoff from the Greek and Turkish mainland. Salinity and nutrient data collected during the INTERREG-I project are used to develop budget calculations and empirical models according to the LOICZ biogeochemical modelling guidelines. The results of the study indicate that the dissolved inorganic nitrogen and phosphorus fluxes imported into the NE Aegean through the Dardanelles are less important than it was believed in the past. Overall, the system acts as a net sink of DIN and DIP, as well as being a net producer of organic matter, as primary production exceeds respiration. Moreover, the system appears to fix more nitrogen than is lost through denitrification.